Development of oligomannose-coated liposome-based nasal vaccine against human parainfluenza virus type 3 - Senchi, Kyosuke; Matsunaga, Satoko; Hasegawa, Hideki; Kimura, Hirokazu; Ryo, Akihide (Frontiers in Microbiology, 2013)
Human parainfluenza viruses (HPIVs) are the etiologic agents of lower respiratory infections and pneumonia in infants, young children and immunocompromised hosts. The overarching goal for the prevention of HPIV infection is the development of an effective vaccine against HPIVs. In the present study, we investigated the effectiveness of oligomannose-coated liposomes (OMLs) as an antigen-delivery system in combination with a synthetic double-stranded RNA analog for the induction of mucosal and systematic immunity against HPIV3. Full-length hemagglutinin-neuraminidase (HN) protein was synthesized using the wheat germ cell-free protein production system and then encapsulated into OML to serve as the antigen. Intranasal administration of the HN-filling OML (OML-HN) with the synthetic double-stranded RNA adjuvant, polyriboinosinic-polyribocytidylic acid [poly(I:C)] generated significant viral-specific systemic and mucosal immune responses as evidenced by the prominent induction of serum IgG and nasal wash IgA, respectively. On the other hand, no significant immune responses were observed in mice immunized with OML-HN without the adjuvant. Furthermore, serum from mice immunized with OML-HN plus poly(I:C) significantly suppressed viral infection in cell culture model. Our results provide the first evidence that intranasal co-administration of OML-encapsulated HN with the poly(I:C) adjuvant augments the viral-specific immunity against HPIV3.